2012
DOI: 10.1111/j.1365-2494.2012.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grazing and precipitation on herbage production, herbage nutritive value and performance of sheep in continental steppe

Abstract: The present study highlights the effects of sheep grazing and precipitation on herbage and animal performance in a grazed steppe of Inner Mongolia. Experimental data were collected during grazing periods of four consecutive years (2005–2008), and effects were analysed across a gradient of seven grazing intensities. Variation in annual precipitation, reflected by the effect of ‘year’, was the major factor affecting herbage; i.e., the production and nutritive value of herbage increased with increasing precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 30 publications
7
31
1
Order By: Relevance
“…It may therefore be concluded that the herd mobility patterns observed in the Altay-Dzungarian region is balanced for the seasonal variability in herbage quality (Yoshihara et al 2013). With values of approximately 0.05 to 2.5 kg DM of above-ground herbaceous biomass per kilogramme live weight and day, the herbage allowance in the study region was at the lower end of values reported for pastures in Inner Mongolia (0.7 to 26.4 kg DM per kilogramme live weight; Schönbach et al 2012;Bösing et al 2014). According to Lin et al (2011) who categorized herbage allowances (kg DM kg −1 live weight), the values obtained in our study correspond to the classes 'heavy grazing' and 'very heavy grazing' during all seasons.…”
Section: Quantity and Quality Of Herbagementioning
confidence: 75%
See 4 more Smart Citations
“…It may therefore be concluded that the herd mobility patterns observed in the Altay-Dzungarian region is balanced for the seasonal variability in herbage quality (Yoshihara et al 2013). With values of approximately 0.05 to 2.5 kg DM of above-ground herbaceous biomass per kilogramme live weight and day, the herbage allowance in the study region was at the lower end of values reported for pastures in Inner Mongolia (0.7 to 26.4 kg DM per kilogramme live weight; Schönbach et al 2012;Bösing et al 2014). According to Lin et al (2011) who categorized herbage allowances (kg DM kg −1 live weight), the values obtained in our study correspond to the classes 'heavy grazing' and 'very heavy grazing' during all seasons.…”
Section: Quantity and Quality Of Herbagementioning
confidence: 75%
“…These circumstances may be aggravated according to climate change predictions for the Altay-Dzungarian region that foresee an increase in the average annual temperature, more frequent and prolonged summer droughts and temporal shifts of precipitation from summer to winter (Angerer et al 2008;Lkhagvadorj et al 2013a;Hilker et al 2014;Liao et al 2014a). Moreover, herd management such as daily herding practices and grazing duration, livestock numbers and herd composition are known to affect the occurrence, frequency, distribution and growth of grassland species and thus herbage yield and its nutritive value (Briske et al 2003;Schönbach et al 2012;Kreutzmann 2013a;Lkhagvadorj et al 2013b;Hilker et al 2014).…”
Section: Quantity and Quality Of Herbagementioning
confidence: 99%
See 3 more Smart Citations